(untitled) - English, Bill (San Francisco, Calif., 2003)
Recognizing the need for qualified security professionals, Microsoft has created a new elective exam for the MCSA and MCSE certifications: Implementing and Administering Security in a Microsoft Windows 2000 Network (#70-214). Sybex, winner of "Best Study Guides" in CertCities.com 2002 Readers' Choice Awards, has compiled a stand-out study guide for this exam. This Study Guide provides in-depth coverage of all exam objectives along with practical insights drawn from real-world experience. The contents map directly to official Microsoft exam objectives. Hundreds of challenging review questions and electronic flashcards help you reinforce key knowledge and skills. Real World Scenario sidebars take you beyond the basics, put information in context, and answer the tough "why" and "when" questions. The accompanying CD includes hundreds of challenging review questions, electronic flashcards, and a searchable electronic version of the entire book.
Keywords: Computer networks,Mạng máy tính; Security measures,Examinations,Các biện pháp an toàn,Kỳ thi